KAJIAN ETNOFARMASI ETNIK BUNGKU DI KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI PROVINSI SULAWESI TENGAH - Hermin Hermin; Nurlina Ibrahim; Arsa Wahyu Nugrahani (Universitas Tadulako, 2016)
This study aims to find out and to inventory the types and parts of plants as well as to dig up information about ways of their utilization as remedy used by Bungku people “To Bungku”. It was conducted from August to December 2015 in Bungku Subdistrict, Central Bungku, Morowali Regency, Central Sulawesi. This research is a descriptive study using qualitative methods and snowball sampling technique on 12 informants through data collection by questionnaire. Results of this etnopharmacy study revealed that there were 62 species of medicinal plants divided into 34 familia. The most widely used plants came from familia Euphorbiaceae, Fabaceae and Zingiberaceae, each was as many as 8%. Parts of plant including roots, stems, leaves, flowers, fruits, seeds and bulbs were used in accordance with their function. Leaves were the ones used with the highest percentage (50%). Bungku people used medicinal plants to treat diseases such as kidney stone, diabetes, hemorrhoids, diarrhea, abscess, candidiasis, gout, cancer, hypertension, hypercholesterolemia, dyspepsia, cough, abdominal pain, malaria, hematuria, skin inflammation, headache, fever, bronchitis, dysentery, asthma, stroke, gallstones, urinary tract infections, broken bones, nail-punctured, wound ulcers, burns, hepatitis, appendicitis. Ways of the utilization were very diverse such as boiling then drinking the decoction; crushing then rubbing on the necessary skin; attaching to the body; squeezing then drinking the juice; and heating on the fire. Processing by boiling has the largest percentage, as much as 54%